PENINGKATAN NILAI TAMBAH PRODUK PERIKANAN KELOMPOK USAHA KERUPUK IKAN DI KELURAHAN ANAIWOI KECAMATAN TANGGETADA KABUPATEN KOLAKA - Asni Asni; Anti Landu (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
Fish cracker business group in Anaiwoi Tanggetada Sub District of Kolaka consists of women in a group of businesses and business groups Amar Ma'ruf and Vika Utama. Fish cracker feedstock using milkfish are easy to get and very abundant but has a low economic value (Rp5,000/kg). Some of the obstacles faced by business groups such as the existence of some products have the quality of the results is still low, contained fish bones, the durability of the product very quickly, this constraint includes the process of production, processing and business management are still very traditional. The production equipment are very simple so it was still very difficult when getting large orders in a short time. Methods of training activities are the implementation and use press machine, practice packaging and practice the process of separation of flesh and bone. Implementation of science and technology resulting increase in production is seen from the increase in turnover, more labor, has a stock of raw materials, product diversification, and the marketing.Keywords: Fish Crackers, Training, Practice, Packing Press Machine